A NOTE ON ETHICS AND STRATEGY: DO GOOD ETHICS ALWAYS MAKE FOR GOOD BUSINESS? - Schwab, Bernhard (Strategic Management Journal, 1996)
Viewing business ethics as enlightened self-interest that always pays in the long run is too easy. While reputation can be a valuable asset, not being tied to a particular code of ethics has an option value. The need for widespread laws and regulations that restrict behavior confirms this. Being ethical may cost—it is still worth pursuing if we believe in goals that transcend shareholder value.